Patients as educators in medical student education in forensic psychiatry: a scoping review of the barriers and facilitators - Sharda, Leila (The journal of forensic psychiatry & psychology, 2024)
Patient educator programmes have become a fundamental part of medical student education, delivering rich and transformative learning. However, little is known about the barriers and facilitators to implementing patient educator programmes for medical students in psychiatry and specifically forensic psychiatry. A systematic search of three databases with no date parameters was undertaken in November 2022, using keywords related to medical education, coproduction, patient involvement, and psychiatry. Five papers on patient educator programmes in psychiatry were located. No literature related to patient educator programmes in forensic psychiatry was identified. Facilitators include a robust policy infrastructure and transparent arrangements for safe educational practices alongside a commitment to coproduction and relational working. Barriers include epistemic injustice, the skills of professional facilitators, and a lack of supporting educational theory. There appears to be scope to deliver high-quality medical student education in forensic psychiatry through patient educator programmes with reciprocal benefits for educators such as rehabilitation, skills development, and possibly therapeutic benefits. The educational and therapeutic value of patient as educator programmes in forensic psychiatry are under-researched. Patient as educator programmes in forensic psychiatry require careful consideration regarding risk, while patients’ prior involvement with the criminal justice system may increase stigma and discrimination. The complexity and risks have seldom been considered. It appears a priority to address the knowledge gap identified by this review.